In vitro correction of cystic fibrosis epithelial cell lines by small fragment homologous replacement (SFHR) technique - Bonifazi Emanuela; Nardone Anna; Serafino Annalucia; Bruscia Emanuela; Sangiuolo Federica; Lais Monica; Gruenert Dieter C; Novelli Giuseppe (BMC, 2002)
Abstract Background SFHR (small fragment homologous replacement)-mediated targeting is a process that has been used to correct specific mutations in mammalian cells. This process involves both chemical and cellular factors that are not yet defined. To evaluate potential of this technique for gene therapy it is necessary to characterize gene transfer efficacy in terms of the transfection vehicle, the genetic target, and the cellular processing of the DNA and DNA-vehicle complex. Methods In this study, small fragments of genomic cystic fibrosis (CF) transmembrane conductance regulator (CFTR) DNA, that comprise the wild-type and ΔF508 sequences, were transfected into immortalized CF and normal airway epithelial cells, respectively. Homologous replacement was evaluated using PCR and sequence-based analyses of cellular DNA and RNA. Individual stages of cationic lipid-facilitated SFHR in cultured cell lines were also examined using transmission electron microscopy (TEM). Results We demonstrated that the lipid/DNA (+/-) ratio influences the mode of entry into the cell and therefore affects the efficacy of SFHR-mediated gene targeting. Lipid/DNA complexes with more negative ratios entered the cell via a plasma membrane fusion pathway. Transfer of the DNA that relies on an endocytic pathway appeared more effective at mediating SFHR. In addition, it was also clear that there is a correlation between the specific cell line transfected and the optimal lipid/DNA ratio. Conclusions These studies provide new insights into factors that underlie SFHR-mediated gene targeting efficacy and into the parameters that can be modulated for its optimization.